(n-10)-7n=62

Simple and best practice solution for (n-10)-7n=62 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (n-10)-7n=62 equation:


Simplifying
(n + -10) + -7n = 62

Reorder the terms:
(-10 + n) + -7n = 62

Remove parenthesis around (-10 + n)
-10 + n + -7n = 62

Combine like terms: n + -7n = -6n
-10 + -6n = 62

Solving
-10 + -6n = 62

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + -6n = 62 + 10

Combine like terms: -10 + 10 = 0
0 + -6n = 62 + 10
-6n = 62 + 10

Combine like terms: 62 + 10 = 72
-6n = 72

Divide each side by '-6'.
n = -12

Simplifying
n = -12

See similar equations:

| 1.3x+.4=1.7 | | X^2-400x+20000=0 | | 2x+7(x+3)=9(x-1)+5 | | 8s+15=0 | | 2n^2+13n-24= | | 2z^4-13z^2+36=0 | | 5(n-12)-7n=62 | | 5x-4(x-3)=16 | | 4(4e+1)=12 | | 2x+12-8x=9x-5 | | 5x+15=2x+q | | 3(n-10)-7n=62 | | -9y-39= | | .25+4=18 | | 11m-10m=9m | | 3(n-10)-7n=18 | | 12w-14w=6 | | n-5m=9 | | -2.4x-1=-2.2x+7 | | 5(n-10)-7n=62 | | 9+2=15 | | 17(x-7)=-8-9 | | 3x+4(3x+5)=25 | | 28=2h+18 | | 2x^2-23a+63= | | y+1=-2+7 | | 7(n-12)-52n=62 | | 3px=2q(r-5x)1 | | -2x-1x=-2 | | (2x^2+5-3)=0 | | g-500=225-g | | -(-10+4)+-(-40)= |

Equations solver categories